Preliminary validation of a questionnaire assessing psychological distress in caregivers of patients with malignant mesothelioma: Mesothelioma Psychological Distress Tool—Caregivers. Issue 1 (18th August 2021) - Bonafede, Michela; Chiorri, Carlo; Azzolina, Danila; Marinaccio, Alessandro; Migliore, Enrica; Mensi, Carolina; Chellini, Elisabetta; Romeo, Elisa; Grosso, Federica; Franzoi, Isabella Giulia; Granieri, Antonella; Guglielmucci, Fanny
Abstract: Objective: To develop a short, flexible, and comprehensive tool to measure psychological distress in caregivers of malignant mesothelioma (MM) patients: the Mesothelioma Psychological Distress Tool—Caregivers version (MPDT‐C). Methods: Based on a systematic review of the relevant literature, aspects associated with caregiver distress were derived. Expert researchers/clinicians developed a pool of items for each identified aspect. Content validity was assessed through a multiple mixed‐methods approach. A multicenter study was conducted to explore the factorial structure of the 47‐item MPDT‐C through Bayesian factor analysis. Results: The Bayesian exploratory factor analysis revealed an underlying three‐factor structure. Factors were labeled Secondary Traumatic Stress, Engagement in Caring, and Meaningful Cognitive Restructuring. All scales showed sufficient reliability and corrected item–total correlations. Females scored higher than males for Engagement in Caring. Conclusions: Taking care of malignant mesothelioma patients is a stressful process that influences the caregiver's physical, emotional, and social wellbeing. Our study offers preliminary evidence in support of the adequate psychometric properties of the MPDT‐C, and these should now be replicated. Results suggest that the MPDT‐C is a reliable tool with which to detect the psychological distress of this traumatized population.